2011
DOI: 10.1177/1462474511414782
|View full text |Cite
|
Sign up to set email alerts
|

Traumatization and mental distress in long-term prisoners in Europe

Abstract: This article investigates the prevalence of traumatization and mental distress in a sample of 1055 male European long-term prisoners as part of a wider study of the living conditions of prisoners serving sentences of at least five years in Belgium,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 51 publications
2
31
0
11
Order By: Relevance
“…Research consistently shows that prisoners have extensive histories of psychological trauma prior to incarceration (Gibson et al, ), including childhood trauma (Weeks and Widom, ) and subsequent psychopathology (Driessen et al, ). A history of multiple trauma is common (Dudeck et al, ). Akyüz et al (), in a sample of 101 prisoners, reported that about two‐thirds had a lifetime diagnosis of post‐traumatic stress disorder (PTSD), but figures on prevalence have been wide‐ranging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research consistently shows that prisoners have extensive histories of psychological trauma prior to incarceration (Gibson et al, ), including childhood trauma (Weeks and Widom, ) and subsequent psychopathology (Driessen et al, ). A history of multiple trauma is common (Dudeck et al, ). Akyüz et al (), in a sample of 101 prisoners, reported that about two‐thirds had a lifetime diagnosis of post‐traumatic stress disorder (PTSD), but figures on prevalence have been wide‐ranging.…”
Section: Introductionmentioning
confidence: 99%
“…Akyüz et al (), in a sample of 101 prisoners, reported that about two‐thirds had a lifetime diagnosis of post‐traumatic stress disorder (PTSD), but figures on prevalence have been wide‐ranging. A diagnosis of PTSD according to DSM‐III‐R, DSM‐IV or ICD‐10 criteria among sentenced prisoners has been reported as affecting between 4% and 66% across studies (Goff et al, ; Akyüz et al, ; Dudeck et al, ). There is evidence to suggest that PTSD remains undiagnosed and untreated in prisoners (Wolff et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mauer et al () drew on data collected by the Bureau of Justice Statistics to underline the greater prevalence of mental health problems among lifers when compared with the general population of prisoners; nearly one in five lifers had a mental illness versus one in six in the general prisoner population. Dudeck et al () also found that the prevalence of trauma is significantly higher among long‐term prisoners when compared with the general population and with short‐term prisoners. Long termers are likely to experience the repercussions of trauma more intensely than other individuals exposed to traumatic incidents in part because of the heightened risk of exposure to new traumatic experiences (Dudeck et al., ).…”
Section: Why Should We Pay More Attention To Long Termers and Lifers?mentioning
confidence: 95%
“…The minimum number of years set forth in definitions of long‐term incarceration has gradually increased over time (MacKenzie and Goodstein, : 6 years; Cunningham and Sorensen, : 10 years; Crayton, : 15 years), and this figure tends to be lower in European research when compared with American studies (e.g., Dudeck et al., : 5 years). This trend is reflective of the significant shifts that have occurred in American correctional policy during the last four decades and suggests a higher threshold for what is regarded as excessive punishment.…”
Section: What Constitutes a “Long Termer”?mentioning
confidence: 99%
“…Dabei zeigen ergebnisse in empirischen Untersuchungen an straftäterpopulationen, dass z. b. 12-35 % aller sexualstraftäter über frühkindlichen sexuellen Missbrauch und auch über emotionale Vernachlässigung berichten, aber nur 15 % eine Ptbs entwickeln [9,10,[12][13][14][15]. Auch wenn traumatisierung vielfältige erkrankungen hervorrufen kann, sollte die Diskussion nicht um das trauma und die Ptbs allein, sondern darum geführt werden, was eine weitreichende psychische Destabilisierung verhindert.…”
Section: Moral Versus Sachlichkeit In Der Diskussion Um Traumata In Sunclassified